Communicative language teaching to improve speaking skill - Banda Muñoz, Carmen Gabriela (2023)
The objective of this study is to analyze how the Communicative Language Teaching approach influences the improvement of speaking ability in students of the Marco Aurelio Subía-Batalla de Panupali Educational Institution in the period 2021-2022. Being an experimental design, 68 students belonging to the first year of high school were randomly chosen for both the experimental group and the control group. The research approach is quantitative since it collects quantified data, subject to statistical analysis, applying a pre and post test. In addition, the participation of both groups was required to compare the percentage results. The Cambridge Preliminary English Test KET was used as an instrument and the data analysis was carried out using the Student's T-test of the statistical program (SPSS), which allowed clarifying the hypothesis and determining the existence of significant differences between the means of both groups.